2009
DOI: 10.1007/s00431-009-1071-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cranial epidural hematoma in a neonate by needle aspiration of a communicating cephalhematoma

Abstract: A newborn presented on day 15 of life with an epidural hematoma, extending through a diastatic sutura squamosa in an external cephalhematoma. There was no skull fracture. The cephalhematoma was punctured twice with 24-h interval, reducing both the cephalhematoma and the epidural component. In the absence of neurological signs or symptoms, aspirating a cephalhematoma to evacuate the communicating epidural hematoma in a newborn infant may avoid more invasive surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Noguchi et al [20] reported usefulness of emergent needle aspirate under transcranial ultrasound guidance for a massive EDH secondary to vacuum-assisted delivery. Smets and Vanhauwaert [21] showed the efficacy of aspiration of cephalic hematoma to evacuate a communicating EDH in a newborn infant with food functional recovery. Park et al [22] studied urokinase instillation using the closed suction drain in post-craniotomy EDH as feasible method with no complications and better outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Noguchi et al [20] reported usefulness of emergent needle aspirate under transcranial ultrasound guidance for a massive EDH secondary to vacuum-assisted delivery. Smets and Vanhauwaert [21] showed the efficacy of aspiration of cephalic hematoma to evacuate a communicating EDH in a newborn infant with food functional recovery. Park et al [22] studied urokinase instillation using the closed suction drain in post-craniotomy EDH as feasible method with no complications and better outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…However, the authors never recommend a time frame for evacuation. Other reports have shown the benefit of cephalohematoma aspiration as a means of evacuating a communicating epidural hematoma in newborns [7,8,9,10,11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Because cranial sutures are not unfused and, therefore, head circumference can increase, intracranial hypertension may be compensated explaining the absence of symptoms. Although alternative methods such as trepanation or needle aspiration of epidural hematomas communicating with cephalohematomas were described [2,3], craniotomy is still considered the standard treatment. Follow-up CT or magnetic resonance imaging scans are mandatory.…”
Section: E20mentioning
confidence: 99%